Persepsi Komunikan Konten Dokter Kecantikan di Tiktok Dalam Perspektif Etika Profesi Kedokteran - Hafidhatul Fathany; Nita Novita Sari; Jessica Aura Azaroh (Jurnal Ilmu Komunikasi, 2024)
TikTok users feel helped by the presence of doctors who focus on sharing education about beauty. However, what needs to be underlined is that every doctor must still uphold the ethics of the medical profession and ethics in social media. The purpose of this study is to find out the audience perception of beauty doctor content on TikTok which is associated with medical professional ethics. In this study, the approach used was a qualitative approach with a qualitative descriptive method. To get data, researchers conducted interviews with Tiktok users who regularly consume educational content of beauty doctors on Tiktok. From research, it was found that they were enthusiastic about the existence of these doctors because they could get education. The capacity of doctors must be maximized for the purposes of content education in skincare and makeup on the market. Of course, this is related to medical professional ethics and doctor ethics in social media that have been regulated by medical professional organizations in Indonesia. As a respected profession, doctors must be wise in sharing every content on Tiktok because it is a representation of themselves and their profession.